Administrative Systems as Strategic Drivers of Sustainability and Competitiveness in Logistics Operations - Clenuar, Juvelyn; Aquino, Roland; Calbitaza, Michaela; De Sotto, Roel (JPAIR Multidisciplinary Research, 2026)
Sustainability has become a central priority in logistics, shaped by global regulations, stakeholder expectations, and the need for resilience. Administrative systems—covering organizational structures, policies, management information systems (MIS), and governance mechanisms—are increasingly recognized as strategic drivers of sustainable logistics performance. This narrative literature review synthesizes studies published between 2020 and 2025 to examine four propositions: (H1) effective administrative systems enhance sustainability outcomes; (H2) environmental impacts are more directly influenced than social and economic dimensions; (H3) globally benchmarked, digitally integrated systems outperform traditional/manual approaches; and (H4) alignment of administrative systems with sustainability goals mediates the relationship between logistics efficiency and long-term competitiveness. The review employed a narrative synthesis approach, integrating theoretical perspectives (RBV, Institutional Theory, Dynamic Capabilities) with empirical evidence from global and Southeast Asian contexts. Findings indicate that administrative systems contribute to sustainability through measurement, coordination, compliance automation, and accountability. Environmental outcomes are most strongly affected due to measurability and regulatory pressure, while social and economic impacts remain indirect. Firms adopting digital integration and benchmarking achieve superior performance, and alignment with sustainability goals transforms efficiency gains into durable competitive advantage. The study highlights gaps in causal evidence and SME-focused research, offering contextual insights for Southeast Asian logistics firms.